The Effect of Responsibility and Work Ability on Work Performance of PT. Catur Adiluhur Sentosa Palembang - Suhada Suhada; Nisa Ulul Mafra; Dini Putri Liana (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This research aims to test the hypothesis of the influence of responsibility and work ability on the work performance of employees of PT Catur Adiluhur Sentosa Palembang. The sampling technique is purposive sampling using the Slovin formula with a total sample of 63 respondents. Using test instruments, validity, and reliability. As well as the classic assumption test, namely the normality test, multicollinearity test and heteroscedasticity test. The data analysis technique used is multiple linear regression analysis, correlation coefficient analysis, coefficient of determination. Test the hypothesis, namely t test and F test. The test results conclude that partially there is an effect of responsibility (X1) on work performance (Y) with a significant value of 0.000 <0.05, while the effect of ability (X2) work on work performance (Y) with significant value of 0.063 > 0.05, meaning that there is no significant effect on work performance. Simultaneous F test results obtained a significant value of 0.000 <0.05. It can be concluded that there is a significant effect simultaneously on responsibility and work ability on employee performance at PT Catur Adiluhur Sentosa Palembang. The test results are strengthened by a correlation test of 0.711 and a determination test of 0.505 which shows the results of the discussion and then have a strong relationship. So that it can form an explanation of 50.5%, the remaining part is influenced by other variables not included in the research model, including mental abilities and attitudes.